Analisis Strategi Pemasaran Produk Airku Milik Perumda Air Minum Tirta Binangun Kulon Progo - Ratnaningtyas, Endah Marendah; Permadi, Bayu; Arief, Aditya Ferdiana (SENTRI: Jurnal Riset Ilmiah, 2025)
Marketing strategy has a vital role in increasing sales of "AirKu" products at Perumda Air Minum Tirta Binangun, Kulon Progo Regency. Through the right strategy, Perumda Air Minum Tirta Binangun can be more effective in introducing, promoting, and communicating the value of their products to potential customers. The purpose of this study is to determine how the marketing strategy implemented by Perumda Air Minum Tirta Binangun, Kulon Progo Regency, for AirKu products, and to find out how to formulate an effective marketing strategy. The research method used is a descriptive qualitative method. The population of this study is the marketing unit of AirKu products. The sample in this study is the marketing manager of AirKu products. Data were collected through interviews, observations, and documentation. Data were analyzed using data triangulation, qualitative analysis, and SWOT analysis. The results of this study indicate that the formulation of a new effective marketing strategy is still needed for PERUMDA Tirta Binangun Kulon Progo Drinking Water, namely by utilizing opportunities with a market segmentation approach that is more grouped into types of consumers, overcoming threats is done by monitoring market trends and always adapting to the current market, utilizing the strengths of AirKu products by introducing AirKu products which are local products that are not inferior to other mineral water products. Overcoming weaknesses is done by researching demand from the company's sales partners. This is done to prevent an empty stock of AirKu products at agent, retail, and wholesale partners.